DOES PHYSICAL ACTIVITY AT A YOUNG AGE REALLY MEAN A HEALTHIER ADULTHOOD AND OLD AGE? - Branko Škof (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2012)
Physical education in schools endeavours to develop life patterns through encouraging regular physical activity and sports in childhood and youth, so as to establish a life-long goal that will reflect in an active, healthy lifestyle and consequently in a higher quality of life also in adulthood and old age. This, however, also raises an important question: Are these goals in fact achieved? The purpose of this paper is based on a review of available - particularly longitudinal - studies and aims at determining the extent of the impact of an active lifestyle and an appropriate level of physical fitness in youth on the health, physical activity and lifestyle in later stages of life. Despite the great interest in academic research of the issue, this question has not yet obtained a completely clear answer. The overall conclusion of most significant longitudinal studies around the world is that a physically active lifestyle developed during childhood and adolescence generally transfers to adulthood; however, the links between practising sports / doing physical activity during childhood/adolescence and adulthood are low (r = 0.09 to 0.25). The relationship between the individual stages of life decreases with an increase of the age interval under observation. On the other hand, more advanced training programmes for young people have a greater impact on the physical activity and health status of the same people in later periods of life. Many more extensive longitudinal studies will be required in order to clarify this issue. Nevertheless, a basic finding is clear: only regular and systematic physical activity both in youth and later periods can contribute to better fitness and better health.